APPLICATION OF THE SMART METHOD FOR PROVIDING SCHOLARSHIPS IN HIGH SCHOOLS - Veti Apriana; Sifa Fauziah; Wati Erawati (RADJA PUBLIKA, 2023)
Providing scholarships is an important step to support the nation's best sons and daughters in pursuing education up to the tertiary level. Many agencies and companies provide scholarships as a form of assistance to ensure the sustainability of the nation's next generation in the future. Nevertheless, the implementation of scholarships at the senior high school level still raises questions regarding conformity with the targets and criteria that have been set. This study aims to apply the Simple Multi Attribute Rating Technique (SMART) method in determining scholarship recipients for high school students. By using the SMART method, it is hoped that the selection process for scholarship recipients can be more effective and fair with the criteria used such as class ranking scores, parents' income, number of dependents on parents, and non-academic achievements. The end result of applying the SMART method is in the form of student rankings indicating their chances of getting a scholarship. The higher the ranking obtained, the greater the opportunity for students to receive scholarships, the highest ranking was achieved by student number 19 with an acquisition value of 97, indicating that this student is entitled to a scholarship. This study shows that the SMART method can be implemented in a decision support system to determine scholarship recipients for high school students.